Diagnostic Testing Team-Based Learning - Michael Goedde; Stephen Everse; Christina Wojewoda (Association of American Medical Colleges, 2015)
Abstract Introduction This module uses team-based learning (TBL) to help medical students understand and apply basic concepts of diagnostic testing such as sensitivity, specificity, and predictive values. The module was designed to occupy a single 2-hour session early in an undergraduate medical curriculum. Development of this activity was motivated by our experiences with learners at a variety of levels who continued to struggle with application and interpretation of test characteristics in clinical settings despite being proficient with the basic calculations. TBL was chosen as a format because of its focus on applications and the growing evidence base for its effectiveness in medical education. Methods The session was implemented early in the first course of our medical curriculum, with students who had been introduced previously to basic principles of statistics as well as calculations of test characteristics. Teams of five to seven members were maintained throughout the year. Individual sessions included preparatory material (reading and learning objectives) with which students became familiar in advance, individual and group readiness tests taken at the beginning of the session, and a brief review of any challenging concepts from these tests. After a short break, students spent the bulk of the session working in teams on more complex applications, with each application question followed by simultaneous reporting of answers and faculty-facilitated whole-class discussion. Results This session was implemented for the first time in 2014 and was well received by first-year medical students. Both the overall session and the specific applications were rated as useful or very useful by 76% and 87% of students, respectively. Faculty facilitators were pleased with the levels of engagement and understanding apparent during the session, and students scored a mean of 85.6% on related exam questions. Discussion We made minor revisions to clarify the wording of several questions and plan to implement the session as described here in the coming year, with timing adjusted in response to student feedback to quicken the pace of applications.